Industry payments to hospitalist physicians: a 5‐year analysis of the Open Payments programme from 2014 to 2018. Issue 12 (22nd December 2020) - Pakanati, Krishna C.; Siddamreddy, Suman; Nalleballe, Krishna; Thombre, Vaishali; Sheng, Sen; Veerapaneni, Karthika; Yadala, Sisira; Kapoor, Nidhi; Dandu, Vasuki; Avula, Akshay; Meegada, Sreenath; Bere, Praveen
Abstract: We analysed Open Payments programme data (https://openpaymentsdata.cms.gov ) on industry‐to‐physician payments to hospitalists for the years 2014 to 2018. Payments to hospitalists increased by 106.5% from 2014 to 2018 with food and beverage (38.5%) and compensation for services other than consulting (24.3%) being the highest‐paid categories. Industry payment to hospitalists was highly skewed with top 10 hospitalists receiving more than 30% of the total payments during the study period. The most common drugs associated with payments were anticoagulant medications (apixaban and rivaroxaban). Industry seems to be spending a significant amount of money to increase awareness of medications among hospitalists. Identification of these trends and potential motives of industry spending is critical to address any potential physician bias.